2000
DOI: 10.1111/j.1528-1157.2000.tb00316.x
|View full text |Cite
|
Sign up to set email alerts
|

7‐Nitroindazole Differentially Affects the Anticonvulsant Activity of Antiepileptic Drugs Against Amygdala‐Kindled Seizures in Rats

Abstract: Summary:Purpose: The objective of this study was to evaluate the interaction of the preferential brain nitric oxide synthase (NOS) inhibitor, 7-nitroindazole (7-NI), with conventional antiepileptic drugs (AEDs) against amygdala-kindled seizures in rats. Methods: Experiments were performed on fully kindled rats. Adverse effects were evaluated with the rotorod test, which assesses motor coordination, and the passive-avoidance task, which assesses memory. Plasma levels of AEDs were measured by immunofluorescence.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2004
2004
2010
2010

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…), has an anticonvulsant effect in the different model of experimental epilepsy. 31,53,56 In contrast, Czuczwar et al 57 reported that L-arginine, at a dose of 500 mg/kg, did not affect the convulsive threshold for the clonic phase of PTZinduced seizures. Although, the earlier effect was seen in the L-arginine + ascorbic acid administered group compared with L-arginine administered group, we may conclude that L-arginine (500 mg/kg, i.p.)…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…), has an anticonvulsant effect in the different model of experimental epilepsy. 31,53,56 In contrast, Czuczwar et al 57 reported that L-arginine, at a dose of 500 mg/kg, did not affect the convulsive threshold for the clonic phase of PTZinduced seizures. Although, the earlier effect was seen in the L-arginine + ascorbic acid administered group compared with L-arginine administered group, we may conclude that L-arginine (500 mg/kg, i.p.)…”
Section: Discussionmentioning
confidence: 95%
“…These results are consistent with previously reported findings. 22,31,35,56 The mechanism of these contradictory effects of L-NAME and 7-NI on penicillininduced epileptiform activity is still unclear. However, these apparently divergent data do not exclude either NO might play a different role in various models of epileptic disorders or it may act as an anticonvulsant or as a proconvulsant agent depending on the experimental procedures and particular brain structures involved as suggested by several reports.…”
Section: Discussionmentioning
confidence: 99%
“…These results are consistent with the report that the anti-convulsant action of pentobarbital was augmented when co-administered with 7-NI (100 mg/kg, i.p.) against amygdala-kindled seizures in rats (43). Similarly, it has been reported that the potentiation of the anti-convulsant action of barbiturates by pre-treatment with 7-NI in picrotoxin-induced seizures in rats and audiogenic seizures in DBA/2 mice (27,28).…”
Section: Discussionmentioning
confidence: 96%
“…Although it is believed that NO exerts a import role on neuronal hyperexcitability evidenced in several seizure disorders, (De Sarro et al, 1996; Paoletti et al, 1998; Borowicz et al, 2000; Itoh et al, 2004; de Vasconcelos et al, 2004; Kato et al, 2005), it is difficult to make a clear conclusion on the involvement of this free radical in epilepiform activity. The determining factor for such a discrepancy is not known, but one might argue that methodological differences may account for it.…”
Section: Discussionmentioning
confidence: 99%